2014
DOI: 10.3402/jev.v3.24384
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of multidrug‐resistant, breast cancer–derived microparticles

Abstract: Cancer multidrug resistance (MDR) occurs when cancer cells evade the cytotoxic actions of chemotherapeutics through the active efflux of drugs from within the cells. Our group have previously demonstrated that multidrug-resistant breast cancer cells spontaneously shed microparticles (MPs) and that these MPs can transfer resistance to drug-responsive cells and confer MDR on those cells in as little as 4 h. Furthermore, we also showed that, unlike MPs derived from leukaemia cells, breast cancer–derived MPs displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 66 publications
4
52
0
Order By: Relevance
“…These results suggest that these proteins are important for stabilizing Pgp in MPs (Pokharel et al 2014). Among the identified proteins, CD44, ezrin, radixin and moesin appeared to be involved in the resistance phenotype and metastasis (Donatello et al 2012).…”
Section: Microparticles and Cancer Resistancementioning
confidence: 83%
See 3 more Smart Citations
“…These results suggest that these proteins are important for stabilizing Pgp in MPs (Pokharel et al 2014). Among the identified proteins, CD44, ezrin, radixin and moesin appeared to be involved in the resistance phenotype and metastasis (Donatello et al 2012).…”
Section: Microparticles and Cancer Resistancementioning
confidence: 83%
“…Therefore, it has been suggested that ezrin is related to Pgp stabilization in MPs and incorporation by the drug-sensitive recipient cells (Brambilla et al 2012;Jaiswal et al 2013;Luciani et al 2002). Pokharel et al (2014) also observed CD73 loaded in the MPs derived from MDR breast cancer cells. Their data suggest that Pgp interacts with CD73 along with CD44 in MPs, which further suggests that CD73 may also participate in the MDR phenotype transfer from solid tumor cells to recipient cells (Pokharel et al 2014).…”
Section: Microparticles and Cancer Resistancementioning
confidence: 93%
See 2 more Smart Citations
“…55) In particular, when Ezr and Msn are silenced by siRNA in parental cells (P-gp-recipient cells), the expression of P-gp is significantly increased by the co-incubation with SMVs compared to that in the case of control and Rdxsilenced parental cells.…”
Section: )mentioning
confidence: 99%